Disparitas Putusan Hakim Nomor 115/Pid.Sus/2023/PN Brb Dengan Putusan Hakim Nomor 116/Pid.Sus/2023/PN Brb Mengenai Tindak Pidana Jual Beli Narkotika - Arianda, Hafiz Satria; Nahdiya Sabrina (Postgraduate University of Merdeka Malang, 2024)
This research discusses criminal disparities, namely the imbalance in the application of sentences by judges for the same or comparable crimes without valid reasons. This research focuses on disparities in Judge's Decision Number 115/Pid.Sus/2023/Pn Brb and Judge's Decision Number 116/Pid.Sus/2023/Pn Brb regarding narcotics buying and selling cases. The research method used is the normative legal method. The results of the analysis show that disparities in judges' decisions are caused by legal factors (legislation), internal factors of the judge (personal condition of the judge), and external factors (condition of the defendant at trial). In Decision Number 115/Pid.Sus/2023/PN Brb, the judge took into account the history of the defendant who had been convicted of a narcotics crime in 2013 and served a sentence of 8 years and 6 months. The judge sentenced him to 7 years in prison and a fine of IDR 1 billion, taking into account aggravating circumstances such as not supporting the government's program to eradicate narcotics and a history of previous convictions. Meanwhile, in Decision Number 116/Pid.Sus/2023/PN Brb, the judge sentenced him to 5 years and 3 months in prison and a fine of IDR 1 billion, taking into account aggravating circumstances such as not supporting government programs and disturbing the community. If the fine is not paid, the defendant will serve an additional 3 months in prison Keywords: Disparity, Judge's Deci-sion, Buying And Selling Narcotics